Islamic Education and Religious Moderation: A Case Study of the Pancasila Student Project - Nur Ahmad; Farandika Nanda Pratama; Nusaibah Nusaibah; Miftakhul Jannah (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
The high number of intolerance cases in the school environment, especially junior high school students, shows the urgency of internalizing religious moderation in education. This has made the Ministry of Religious Affairs of the Republic of Indonesia make efforts to internalize religious moderation policies through P5 “Projek Penguatan Profil Pelajar Pancasila”. Researchers found one school, SMP 1 Undaan, which integrates moderation values through P5 with the project “Outingclass Tempat Ibadah” so that this study aims to describe the concrete form of integration of religious moderation in P5, analyze the implementation of internalization of moderation values through the project, and explore the role of religion teachers in strengthening religious moderation in schools. This research uses the type of field research with data collection methods through observation, interviews, and documentation and analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the “Outingclass Places of Worship” project became a bridge in building harmony of religious diversity in schools. This visit not only enriches students' insights but also strengthens the moderation values of tasamuh (tolerance), tahadhdhur (civilized), and musawah (equality). In addition, the role of religious teachers is inseparable in guiding students, providing role models, and ensuring the sustainability of moderation values in the project so that this research can be a reference for other schools in implementing religious moderation policies through the P5 program to create an inclusive, harmonious and tolerant school climate.